Death at sea : Montalbano's early cases - Camilleri, Andrea (Camilleri, Andrea. Inspector Montalbano mystery., 2018)
"You either love Andrea Camilleri or you haven't read him yet. Each novel in this wholly addictive, entirely magical series, set in Sicily and starring a detective unlike any other in crime fiction, blasts the brain like a shot of pure oxygen... transporting. Long live Camilleri, and long live Montalbano." --A.J. Finn, #1 New York Times bestselling author of The Woman in the Window Set on the Sicilian coast, a collection of eight short stories featuring the young Inspector Montalbano In 1980s Vigàta, a restless Inspector Montalbano brings his brash yet clear-sighted investigative style to eight enthralling cases. Death at Sea finds the detective seeking to bring justice to crimes -- from those involving jilted lovers and deadly family affairs to an encounter featuring the assassination attempt against the Pope to murders in unexpected places -- always with the mafia not far behind. This collection is an essential addition to any Inspector Montalbano fan's bookshelf and an excellent way to introduce new readers to Andrea Camilleri's unforgettable slice of Sicily.